Causes et conséquences de l’hyperconnectivité professionnelle : au-delà de la responsabilité individuelle des travailleurs et travailleuses - Geneviève Richard (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper provides a review and explanation of the various causes and effects associated with workplace hyperconnectivity, and seeks to highlight the need for both legislative and management solutions that take current technological realities into consideration. Professional hyperconnectivity is defined as the almost constant use of information and communication technologies (ICT) by workers so that they may remain connected to their professional environment. This occurs in workers of all backgrounds and hierarchical positions. It is likewise associated with many deleterious effects for the health of these workers, their professional trajectories, their work-life balance, and even the organization of work itself. Some individual self-discipline initiatives (e.g., turning off company devices at the end of the workday) may be effective for certain workers. However, they are far from a panacea, given the many factors beyond the workers’ control which motivate or even enjoin them to remain connected at all times, wherever they are.